Ligand-independent activation of AhR by hydroquinone mediates benzene-induced hematopoietic toxicity. (1st March 2022) - Yang, Xiaohan; Li, Chao; Yu, Gongchang; Sun, Lei; Guo, Sumei; Sai, Linlin; Bo, Cunxiang; Xing, Caihong; Shao, Hua; Peng, Cheng; Jia, Qiang
Abstract: Although it has been well recognized that benzene exposure can cause hematopoietic disorders such as aplastic anemia and leukemia, the underlying molecular mechanism remains to be fully understood. Emerging evidence indicated that aryl hydrocarbon receptor (AhR) plays important roles in hematopoietic and immune systems. This study investigated the activation of aryl hydrocarbon receptor (AhR) by hydroquinone (HQ) and its role in HQ-induced DNA damage and apoptosis in cultured human lymphocytes (JHP cells). We also investigated the effect of ROS on AhR activation and functions in JHP cells exposed to HQ with and without regulator including N-acetyl-l -cysteine (NAC), a potent antioxidant, and tert-butylhydroquinone (TBHQ), a Nrf2 activator. Results showed that HQ can cause oxidative stress, DNA damage and apoptosis. Pretreatment of an AhR antagonist (CH223191) can significantly increase the cell survival and mitigate HQ-induced toxicities such as DNA damage and apoptosis. We found that HQ can obviously increase expressions of total protein of AhR and prompt nuclear translocation compared to the control group. Interestingly, NAC can block HQ-induced AhR activation and DNA damage and apoptosis. Conclusively, our results indicated that HQ toxicity is mediated by AhR which is in turn regulated by ROS generated by HQ. The interaction between AhR and ROS drive and amplify the hematopoietic toxicity of HQ. This study provided new insights of mechanism and potential targets for the prevention and treatment to benzene-induced hematopoietic toxicity. Graphical abstract: Image 1 Highlights: Hydroquinone (HQ) induced nuclear translocation of AhR. Inhibition of both AhR and ROS attenuated HQ-induced DNA damage and apoptosis. AhR inhibition attenuated HQ-induced ROS production. ROS inhibition attenuated HQ-induced AhR activity.